Analisis Faktor-faktor Penyebab Rendahnya Minat Baca Siswa Kelas V SD Negeri 184 Pekanbaru - Aini, Orin Tul; Kurniaman, Otang; Antosa, Zariul (Asian Journal of Early Childhood and Elementary Education, 2024)
This research aims to describe the factors that cause the low interest in reading in class V students at SD Negeri 184 Pekanbaru. The subjects of this research were 114 class V students, with 5 students from class VA, 5 students from class VB, and 4 people from class VC. Apart from fifth grade students who were used as research subjects. The method in this research uses a qualitative descriptive approach. Data collection techniques in this research use including interviews, observation, documentation. The data processing and analysis process is carried out by collecting data by reduction, the reduced data is then presented in a data presentation, then after that the data is verified to draw conclusions. The conclusions in this research were made with the aim of answering the problem formulation in this research, namely "what are the factors causing the low interest in reading in class V of SD Negeri 184 Pekanbaru?" namely as follows: 1) the factors causing the low interest in reading in class V students at SD Negeri 184 Pekanbaru are due to the lack of encouragement from parents and families in supporting the development of children's interest in reading and familiarizing their children with reading habits. 2) Interest in reading does not always appear by itself, but requires effort and effort from both the family and the environment, both the school and social environment outside of school, who have the habit of enjoying reading so that children's interest in reading can continue to develop.